Experimental studies on soil compaction by the DM-58 combined vibratory roller in the field conditions - Krayushkin A.S.; Tyuremnov I.S.; Shorohov D.A. (Научно-технический вестник Брянского государственного университета, 2025)
The purpose of the presented work is to obtain experimental data to evaluate the technological capabilities of the DM-58 roller and verify the mathematical model of the interaction of a vibrating roller with the ground. Experimental studies were performed on a DM-58 vibrating combined roller with compaction of sandy-gravelly soil with a layer thickness of 0.5…0.55 m. The studies were conducted at two sites with similar soil and technological conditions. The result of soil compaction after each pass of the DM-58 roller was estimated by the value of the dynamic modulus of soil deformation. The measurement was carried out by the ZORN ZFG 3.0 dynamic loading unit. In the experiment, vertical move-ments of the vibrating roller, acceleration of vertical vibrations of the vibrating roller and the roller frame were recorded. When processing the experimental re-sults, the technology of digital filtering of sensor signals (a low-pass filter with a boundary frequency of 200 Hz) was applied. Data were obtained on the change in the value of the dynamic modulus of soil deformation from the number of passes of the DM-58 roller. In 10…12 passes of the roller, the value of the dynamic modulus of deformation of 30 MPa is achieved. It was found that the span of the vertical vibrations of the roller was, on average, 2…2.5 mm, regardless of the values of the dynamic modulus of deformation. The amplitude values of the accelerations of the vertical vibrations of the roller frame ranged from +4.5…+7.8 to -4.8…-8.1 m/s2 and also did not depend on the values of the dynamic modulus of deformation. The obtained results allow us to evaluate the technological capabilities of the DM-58 roller and verify the mathematical model of soil compaction with ground vibration rollers.